Pragmatic Language in Children with Autism Spectrum Disorder : A Systematic Review - Sudrajad, Kiyat; Dwi Purnaningrum, Windiarti (Politeknik Kesehatan Kemenkes Surakarta, 2025)
Background: Autism Spectrum Disorder (ASD) is a neurodevelopmental condition that affects an individual's social, communication, and behavioral abilities. According to data from the Centers for Disease Control and Prevention (CDC), the prevalence of ASD in the United States is approximately 1 in 44 children (CDC, 2021). Objectives: To analyze pragmatic abilities in children with ASD and learning materials for scientific research writing, while also providing additional information regarding pragmatic abilities in children with ASD. Methods: This study is a systematic review. This study uses data from previous studies. A quantitative systematic review combines findings from various independent studies and produces a statistical summary of those findings (Last, 2001 in Murti, 2018). Results: Children with ASD exhibit a continuous state of language difficulties, with social communication skills being a significant issue. Conclusion: Semantic-pragmatic communication skills constitute a core impairment in the narratives of children with ASD. pragmatic aids and deficits in global executive function when compared to children with typical development. Keywords: Pragmatic Language, ASD, Systematic review